2021
DOI: 10.1037/bne0000418
|View full text |Cite
|
Sign up to set email alerts
|

Chronic social defeat stress mouse model: Current view on its behavioral deficits and modifications.

Abstract: Stress is the main cause of mood disorders such as depression and posttraumatic stress disorder. Individuals respond to stress differently, as some develop depressive symptoms, whereas others successfully cope with adversity, but it remains unclear what makes some particularly vulnerable to stress. The chronic social defeat stress (CSDS) mouse model, an ethologically valid rodent model that exhibits long-term physiological and behavioral phenotypes similar to depression and anxiety, can imitate individual diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 89 publications
(164 reference statements)
2
23
0
Order By: Relevance
“…Social defeat stress promotes depression via synaptic structural changes in the PFC and amygdala [ 54 ], which affect the maturation of newly generated neurons in the hippocampus [ 55 ] and induce neurovascular pathology [ 56 ]. In the current study, obese mice experiencing CSDS showed a significant decline in social functioning and depressive-like behaviors, similar to previous reports [ 57 , 58 ]. In this study, obesity per se did not induce depression, but increased the risk thereof under social stress.…”
Section: Discussionsupporting
confidence: 92%
“…Social defeat stress promotes depression via synaptic structural changes in the PFC and amygdala [ 54 ], which affect the maturation of newly generated neurons in the hippocampus [ 55 ] and induce neurovascular pathology [ 56 ]. In the current study, obese mice experiencing CSDS showed a significant decline in social functioning and depressive-like behaviors, similar to previous reports [ 57 , 58 ]. In this study, obesity per se did not induce depression, but increased the risk thereof under social stress.…”
Section: Discussionsupporting
confidence: 92%
“…Social conflicts often happen in a human society, which could be unavoidable stress, leading to reduce the quality of life [ 195 ]. Repeated social defeat stress (SDS) conditionings resulting from the exposure of the rodent to multiple aggressive social encounters appear to be relevant stressor mimicking common types of psychosocial stress seen in humans [ 196 , 197 ]. These findings indicate that SDS models could be more relevant for the psychological stress conditions in human life compared with CRS and FS models.…”
Section: Preclinical Models For Psychological Stress and Deep Craniofacial Pain ( Table 1 )mentioning
confidence: 99%
“…Among these environmental factors, stress - understood as adversity/negative experiences in life—has been shown to enhance vulnerability to the rewarding effects of cocaine and other drugs of abuse ( Aguilar et al, 2013 ; Rodríguez-Arias et al, 2013 ; Vannan et al, 2018 ). Among the different types of stress, social stress is currently the most common, and can be modelled in experimental animals with the chronic/repeated social defeat (SD) paradigm, which is known to have predictive power ( Vasconcelos et al, 2015 ; Patel et al, 2019 ; Wang et al, 2021 ; García-Pardo et al, 2022 ). Several studies have shown an increase in the rewarding effects of cocaine in the conditioned place preference (García-Pardo et al, 2019; Calpe-López et al, 2020 ; Montagud-Romero et al, 2020 ) and self-administration ( Holly EN.…”
Section: Introductionmentioning
confidence: 99%